Synthesis and cytotoxic evaluation of novel dihydrobenzo[h]cinnoline-5, 6-diones. Issue 43 (21st October 2015) - Dang Thi, Tuyet Anh; Decuyper, Lena; Thi Phuong, Hoang; Vu Ngoc, Doan; Thanh Nguyen, Ha; Thanh Nguyen, Tra; Do Huy, Thanh; Huy Nguyen, Hung; D'hooghe, Matthias; Van Nguyen, Tuyen
Graphical abstract: Abstract: A convenient one-pot multicomponent synthetic approach was developed en route to novel functionalized dihydrobenzo[ h ]cinnoline-5, 6-diones using 2-hydroxy-1, 4-naphthoquinone, methylhydrazine, and a variety of aromatic aldehydes. Fifteen new derivatives were thus prepared and subsequently evaluated in terms of their cytotoxicity profile, revealing a promising anticancer activity of nine of the compounds against KB and Hep-G2 human tumor cell lines.